Optimization of Directional Long Boreholes Unloading Gas Extraction Process and Application Research - Chunhua Zhang; Yuqi Li (Applied Sciences)
In order to optimize the pressure relief gas extraction process for the 1504 working face in East 2 of Dalong Coal Mine based on its mining and gas conditions, a physical model of pressure relief gas extraction in the airspace using two preliminary extraction processes—a high-level oblique borehole and a directional long borehole—was established using COMSOL 6.2 software. The changes in the gas extraction effect of high-level oblique boreholes were analyzed through a simulation of the advancement of the working face, and the reasons for the low utilization rate of the high-level oblique boreholes were outlined. The effects of the horizontal distance of the directional long boreholes from the side of the air return lane, the borehole spacing, and the negative pressure of the boreholes on the gas extraction effect were analyzed, and the gas extraction process of the directional long boreholes was optimized and applied in the field. The results showed that the directional long borehole gas extraction process had a better extraction effect, a higher borehole utilization rate, and superior cost savings, and was thus was the preferred process. Additionally, the optimal parameters were a 30 m horizontal distance of the boreholes from the side of the air return lane, a 30 m spacing between the boreholes, and a 20 kPa negative extraction pressure.